Trials and tribulations of pancreatic cancer immunotherapy. (28th April 2021) - Principe, Daniel R.; Korc, Murray; Kamath, Suneel D.; Munshi, Hidayatullah G.; Rana, Ajay
Abstract: Immunotherapy has revolutionized cancer treatment in the last decade, and strategies to re-activate cytotoxic immunity are now standard of care in several malignancies. Despite rapid advances in immunotherapy for most solid cancers, progress in immunotherapy against pancreatic ductal adenocarcinoma (PDAC) has been exceptionally difficult. This is true for several approaches, most notably immune checkpoint inhibitors (ICIs) and GM-CSF cell-based vaccines (GVAX). Though many immunotherapies have been explored in clinical trials, few have shown significant therapeutic efficacy. Further, many have shown high rates of serious adverse effects and dose-limiting toxicities, and to date, immunotherapy regimens have not been successfully implemented in PDAC. Here, we provide a comprehensive summary of the key clinical trials exploring immunotherapy in PDAC, followed by a brief discussion of emerging molecular mechanisms that may explain the relative failure of immunotherapy in pancreas cancer thus far. Highlights: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer related death, with an overall five-year survival rate of less than 10%. Despite rapid progress in the treatment of many solid cancers, immunotherapy has yet to show clear efficacy in PDAC. Several clinical trials have explored immunotherapy in the treatment of PDAC. However, the results of these trials have been mostly disappointing, particularly regarding immune checkpoint inhibitors. Here, we provide a comprehensive summary of the key clinical trials exploring immunotherapy in PDAC, and a brief discussion of emerging mechanisms that may explain the innate resistance of PDAC tumors to immunotherapy.